2022
DOI: 10.7150/jca.71992
|View full text |Cite
|
Sign up to set email alerts
|

From Immunosuppression to Immunomodulation - Turning Cold Tumours into Hot

Abstract: Cancer cells employ various mechanisms to evade and suppress anti-cancer immune responses generating a "cold" immunosuppressive tumour microenvironment. Oncolytic viruses are a promising tool to convert tumour immunosuppression to immunomodulation and improve the efficacy of cancer treatment. Emerging preclinical and clinical findings confirm that oncolytic viruses act in a multimodal scheme, triggering lyses, immunogenic cell death and finally inducing anti-cancer immune responses. In this paper, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…( 41 ) showed that Coxsackievirus A21 (CAVATAK) synergized in anti-cancer efficacy when administered with immune CPIs. A trial assessing CAVATAK with ipilimumab resulted in 50% objective responses in melanoma patients ( 18 , 41 ). Encouraging data have been also reported in a treatment with VALO-D102, an oncolytic vector, encoding for OX40L and CD40L, used in PeptiCRAd cancer vaccine system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 41 ) showed that Coxsackievirus A21 (CAVATAK) synergized in anti-cancer efficacy when administered with immune CPIs. A trial assessing CAVATAK with ipilimumab resulted in 50% objective responses in melanoma patients ( 18 , 41 ). Encouraging data have been also reported in a treatment with VALO-D102, an oncolytic vector, encoding for OX40L and CD40L, used in PeptiCRAd cancer vaccine system.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging data have been also reported in a treatment with VALO-D102, an oncolytic vector, encoding for OX40L and CD40L, used in PeptiCRAd cancer vaccine system. The local administration of PeptiCRAd strongly elevated tumor-specific T-cell responses, inhibited tumor growth, and in combination with anti-PD-1, significantly improved anti-cancer effect ( 18 , 23 ). Similar data have been also reported by Hemminki lab where i.t.…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic viruses are emerging as targeted therapy for MPM due to their ability to destroy tumor cells without affecting non-tumor cells, releasing antigens that activate T cells through dendritic cells. 76 In the case of MPM, therapy with adenoviruses, 77 poxviruses, 78 reoviruses, 79 herpesviruses, 80 and measles virus 81 is being investigated. Virotherapy is one of the most promising alternatives, with various studies showing that human MPM cells are sensitive to many oncolytic viruses through direct cell death or immunomediated mechanisms.…”
Section: Future In the Treatment Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…However, their therapeutic efficacy is not yet optimal due to weak intratumoral virion retention, virus shedding to normal healthy organs, variable infection, and replication efficacy due to the heterogeneity of cancer [ 138 ]. Therefore, the development of new and more potent oncolytic adenoviruses is in high demand [ 139 , 140 ].…”
Section: Limitations Of Adenoviruses In Clinical Trialsmentioning
confidence: 99%